2017
DOI: 10.1039/c7tx00020k
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological implications of mitochondrial localization of CYP2E1

Abstract: Cytochrome P450 2E1 (CYP2E1) metabolizes an extensive array of pollutants, drugs, and other small molecules, often resulting in bioactivation to reactive metabolites. Therefore, it is unsurprising that it has been the subject of decades of research publications and reviews. However, while CYP2E1 has historically been studied in the endoplasmic reticulum (erCYP2E1), active CYP2E1 is also present in mitochondria (mtCYP2E1). Relatively few studies have specifically focused on mtCYP2E1, but there is growing intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 153 publications
(147 reference statements)
1
19
0
Order By: Relevance
“…CYP2E1 is a membrane protein expressed at a high level that is primarily distributed in the ER and mitochondrial membrane (Bièche et al, 2007;Hartman et al, 2017). It is closely related to ER stress, which may be why lung injury in KO mice is not obvious after PM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2E1 is a membrane protein expressed at a high level that is primarily distributed in the ER and mitochondrial membrane (Bièche et al, 2007;Hartman et al, 2017). It is closely related to ER stress, which may be why lung injury in KO mice is not obvious after PM exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Total cell membranes were prepared because it has been shown that brain CYPs are present more in multiple membrane fractions, including microsomal, mitochondrial, and nuclear membranes [ 25 , 26 , 27 ]. The whole brain was used to prepare and extract brain membranes for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The CYP-2 family mainly includes the CYP2B subfamily and CYP2E1. CYP2E1 metabolizes an extensive array of pollutants, drugs, and other small molecules, often resulting in bioactivation to reactive metabolites, which in turn damage mitochondria 37 . HgCl 2induced hepatotoxicity and oxidative stress is partially mediated through its effects on CYP2E1 38 .…”
Section: Effects Of Mercury Compounds On Cytochrome P450mentioning
confidence: 99%